Harmonisation of imaging dosimetry in clinical practice: practical approaches and guidance from the ESR EuroSafe Imaging initiative - Vano, Eliseo; Frija, Guy; Stiller, Wolfram; Efstathopoulos, Efstathios; Granata, Claudio; Loose, Reinhard; Paulo, Graciano; Pekarovic, Dean; Sjöberg, Johan; Donoso-Bach, Lluís (Insights into imaging, 2020)
The European Directive 2013/59/EURATOM requires member states of the European Union to ensure justification and optimisation of the radiological procedures and to include information on patient exposure as part of the report of the examinations. The EuroSafe Imaging campaign of the European Society of Radiology created a working group (WG) on “Dosimetry for imaging in clinical practice” with the aim to help with the dosimetry aspects required by European and national regulations. The primary focus topics were selected and a survey among the experts of the WG, allowed suggesting some initial consensus approaches.